The Ritual that Shapes Everyday Life and Belief World of Alevis: Cem - Bulut, Alican (Journal of Alevism-Bektashism Studies, 2023)
Alevism, in addition to Islam, has embraced and incorporated many belief systems and philosophies, and by developing them into social institutions, it has succeeded in creating a way of life that can meet the socio-economic, judicial, and moral needs of the Alevi-Bektashi community within the framework of equality. Cem, which is the collective worship of Alevis, has specific rules. There are rituals called the “On İki Hizmet (Twelve Services)” that are carried out by individuals assigned specific roles during the cem ceremony.Cem rituals generally take place during the autumn and winter months when the agricultural and livestock activities of the community have concluded, and people begin to spend more time at home. Cems are commonly held on the night between Thursday and Friday or during the period when the dede visits the village. Cems are conducted jointly by both women and men under the guidance of dedes or babas.By performing the cem ritual, Alevis pray to Allah, practice religious rituals, socialize, and maintain self-control over their behavior. The Alevi belief system has institutionalized itself with the aim of fostering individuals who are morally upright and spiritually developed (kâmil insan). The community has used cem rituals as a form of education, aiming to teach “kâmil insan”. It is observed that the cem ritual has acquired a different structure compared to its traditional functions in contemporary times.Today, cem rituals have become less functional compared to the past. Within the new socio-economic structure, cems primarily serve the purpose of sustaining the belief system. The desire of Alevis to worship is a significant factor leading to the construction of cemevi (Alevi houses of worship) in modern times. Therefore, the most important function of cemevis today is the collective performance of cem rituals. This serves to keep Alevi beliefs and teachings alive.In addition to performing religious worship, cemevis today also serve as centers for social assistance and solidarity, aiming to meet the needs of those in need. They provide scholarships to impoverished students, organize preparatory courses for students who are unable to attend regular courses, distribute food and clothing to pre-identified families, arrange circumcision ceremonies for children, provide financial and moral support to young couples who are unable to marry, offer free healthcare services to those who cannot afford medical expenses or doctor visits.Within the cemevi premises, soup kitchens operate on specific days of the week, distributing meals to the poor and needy individuals. Through these initiatives, Alevi community members are able to extend their helping hand and reach out to those in need, fostering social solidarity and unity.
Keywords: Alevism; cem; cemevi; stories/rumors; social functions